Pesan Nonverbal pada Web Series “Mengakhiri Cinta dalam 3 Episode” - Naufal Asyrof Rizky; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
As the rapid progress in cyberspace or we are familiar with the internet, now filmmakers no longer rely on television and the mainstream media to showcase work. As in this study which discusses a series of shows on social networks that can be enjoyed anywhere and anytime, commonly referred to as "web series". With social reality construction theory and mass media, constructivism paradigm and Charles Sanders Pierce's semiotic analysis used to carry out this research, researcher try to analyze nonverbal messages through the signs that appear in this show. Not many people pay attention when watching a show. The research results obtained by researchers in the form of nonverbal messages such as eye-sights, facial expressions and body language are significantly deeper than verbal messages.